Mucocele Causing Hydropic Gallbladder. (21st September 2018) - Hassan, Muhammad Masood; Naab, Tammey
Abstract: Hydropic gallbladder is a rare condition resulting from gallstone impaction, tumors, and narrowing of the cystic duct. Histopathological examination is essential in guiding optimal patient management. We present a case of a 62-year-old Hispanic male with right upper quadrant pain. Diagnostic abdominal ultrasound was significant for a 1.2-cm stone at the gallbladder neck with a 0.6-cm thickened gallbladder wall. Laparoscopic cholecystectomy was performed. A calculus was not found. Calcification in the solidified mucocele represented the stone seen on imaging. Gross examination revealed thickened hard gallbladder. Cut sections revealed dense yellow material filling and distending the lumen. Differential diagnoses include hyalinizing cholecystitis, xanthogranulomatous cholecystitis, and gallbladder carcinoma. Histology revealed a solidified eosinophilic secretion having a central cholesterol core densely adherent to flattened inflamed mucosa. Gram and GMS stains were negative. The secretion was PAS positive and diastase resistant. Epithelial mucins and mucopolysaccharides would yield that reaction. Hypersecretion of glycoproteins and variant of mucocele were diagnostic possibilities. Such mucocele-like sludge, while classically reported in the veterinary setting, has also been reported in association with acute cholecystitis, retained gallbladder stump after incomplete cholecystectomy, and in patients with sickle cell disease. Histopathological evaluation is critical in assessing a partially calcified gallbladder mass in an older patient, especially when ultrasound is inconclusive. Hardened gallbladder mucocele can grossly mimic GB carcinoma.